Gene expression alterations in the cerebellum and granule neurons of Cstb(-/-) mouse are associated with early synaptic changes and inflammation. - Tarja Joensuu; Saara Tegelberg; Eva Reinmaa; Mikael Segerstråle; Paula Hakala; Heidi Pehkonen; Esa R Korpi; Jaana Tyynelä; Tomi Taira; Iiris Hovatta; Outi Kopra; Anna-Elina Lehesjoki (PLoS ONE)
Progressive myoclonus epilepsy of Unverricht-Lundborg type (EPM1) is an autosomal recessively inherited neurodegenerative disease, manifesting with myoclonus, seizures and ataxia, caused by mutations in the cystatin B (CSTB) gene. With the aim of understanding the molecular basis of pathogenetic events in EPM1 we characterized gene expression changes in the cerebella of pre-symptomatic postnatal day 7 (P7) and symptomatic P30 cystatin B -deficient (Cstb(-/-) ) mice, a model for the disease, and in cultured Cstb(-/-) cerebellar granule cells using a pathway-based approach. Differentially expressed genes in P7 cerebella were connected to synaptic function and plasticity, and in cultured cerebellar granule cells, to cell cycle, cytoskeleton, and intracellular transport. In particular, the gene expression data pinpointed alterations in GABAergic pathway. Electrophysiological recordings from Cstb(-/-) cerebellar Purkinje cells revealed a shift of the balance towards decreased inhibition, yet the amount of inhibitory interneurons was not declined in young animals. Instead, we found diminished number of GABAergic terminals and reduced ligand binding to GABAA receptors in Cstb(-/-) cerebellum. These results suggest that alterations in GABAergic signaling could result in reduced inhibition in Cstb(-/-) cerebellum leading to the hyperexcitable phenotype of Cstb(-/-) mice. At P30, the microarray data revealed a marked upregulation of immune and defense response genes, compatible with the previously reported early glial activation that precedes neuronal degeneration. This further implies the role of early-onset neuroinflammation in the pathogenesis of EPM1.